2016
DOI: 10.1016/j.visres.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent lightness affects perceived contrast

Abstract: a b s t r a c tPerceived contrast of a grating varies with its background (or mean) luminance: of the two gratings with the same photometric contrast the one on higher luminance background appears to have higher contrast. Does perceived contrast also vary with context-dependent background lightness even when the luminance remains constant? We investigated this question using a stimulus in which two equiluminant patches (''context squares", CSs) appear different in lightness. First we measured the lightness eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…On the other hand, several studies have dealt with the effectiveness of lower-and higher-luminance components with respect to the background that spanned the entire achromatic gamut of the visual field from black to white. It has been reported that the on and off signals with respect to the adapting field (gray) in the achromatic channel were mediated by separate mechanisms on unipolar contrast adaptation (Beer & MacLeod, 2000;Sato, Motoyoshi, & Sato, 2016) and spatial interactions in perceived contrast (Pamir & Boyaci, 2016;Sato, Motoyoshi, & Sato, 2012). In the present study, the average stimulus observation time was approximately 2.5 s, and thus, the light adaptation to the luminance levels of each image should be weak even if it occurred.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the other hand, several studies have dealt with the effectiveness of lower-and higher-luminance components with respect to the background that spanned the entire achromatic gamut of the visual field from black to white. It has been reported that the on and off signals with respect to the adapting field (gray) in the achromatic channel were mediated by separate mechanisms on unipolar contrast adaptation (Beer & MacLeod, 2000;Sato, Motoyoshi, & Sato, 2016) and spatial interactions in perceived contrast (Pamir & Boyaci, 2016;Sato, Motoyoshi, & Sato, 2012). In the present study, the average stimulus observation time was approximately 2.5 s, and thus, the light adaptation to the luminance levels of each image should be weak even if it occurred.…”
Section: Discussionmentioning
confidence: 52%
“…For example, the wavy samples have some overall luminance gradient from shading. Considering that changes in perceived lightness from the luminance gradient affect the apparent contrast of a grating (Pamir & Boyaci, 2016), the luminance gradient from global surface shape could affect the quality of material perception. These possible effects of macro-shading patterns could be investigated using samples with macroscale shapes but without strong specular reflections.…”
Section: Limitations Of Our Findingsmentioning
confidence: 99%
“…Contextual effects are ubiquitous in perception and it is thus ultimately essential to consider them for understanding binocular percepts during natural vision. For example, the same patch of gray can be perceived to be a different shade depending on whether it is on a dark or light background ( Adelson, 1993 ) and the same grating can appear to have different contrast depending on its surrounding context ( Pamir & Boyaci, 2016 ; Xing & Heeger, 2001 ). An effect known as surround suppression, in which a pattern seems to have a higher or lower contrast depending on the visual similarity of the surrounding area, can be observed both in early cortical neurons and psychophysically ( Xing & Heeger, 2001 ).…”
Section: Introductionmentioning
confidence: 99%